Harun Farocki's Asignifying Images - Claudio Celis Bueno (tripleC: Communication, Capitalism & Critique)
With the recent publication of Signs and Machines by Maurizio Lazzarato and Critical Semiotics by Gary Genosko, the concept of asignifying semiotics introduced by Félix Guattari in the late 1960s is regaining attention. This revived interest responds largely to the rise and consolidation of new technologies of power based on algorithmic control and Big Data analysis. In the new context of informational capitalism, Guattari’s asignifying semiotics appears as a powerful conceptual tool for exploring the role of information technologies in the reproduction of capitalist power relations. This article contributes to this discussion by introducing the notion of asignifyng images in order to explore the role that images acquire in this new age of algorithmic control. To achieve so, this article focuses on Harun Farocki's concept of operational images and reads some of his audiovisual work through the prism of Guattari’s asignifying semiotics. More specifically, this article compares the representational account of labour in the film Workers Leaving the Factory (1995) with the non-representational perspective deployed by the video installation Counter-Music (2004). This distinction between a representational and a non-representational framework responds to the distinction between signifying and asignifying semiotics. By comparing these two perspectives this article attempts to delineate some key elements for a broader reflection upon the transformation of the role of images in the reproduction of contemporary capitalism.